A single injection of corifollitropin alfa supplemented with human chorionic gonadotropin increases follicular recruitment and transferable embryos in the rabbit - Viudes-De-Castro, María P.; Marco-Jiménez, Francisco; Más Pellicer, Alba; García-Domínguez, Ximo; Talavan, Amparo; Salvador Vicente, José (Blackwell Verlag GmbH, 2020)
Superovulation protocols are designed to achieve maximum embryo yields. Nevertheless, ovarian response control and the quality of obtained embryos are still a challenge. On the other hand, to save the superovulated embryos until their subsequent use, it is usual to cryopreserve them, so it is also crucial to assess their cryotolerance. The aim of this study was to compare the efficacy of a single injection of corifollitropin alfa (FSH‐CTP) alone or supplemented with human chorionic gonadotropin (hCG) and to determine the impact of this stimulation on in vitro and in vivo development of fresh or devitrified embryos. Our outcomes showed that ovulation rate and recovered embryos were significantly increased when hCG was used. In vitro development of fresh and devitrified embryos and survival at birth were not significantly affected by superstimulation treatment. Results of this study suggest that a single injection of long‐acting FSH‐CTP supplemented with hCG can be effectively used in rabbits to elicit an increase in ovulation rate and number of recovered embryos. Furthermore, we demonstrated that hCG supplementation had no negative effects in embryo cryosurvival and development, showing similar survival rate at birth than FSH‐CTP alone group.